PENGARUH LATIHAN CIRCUIT TRAINING TERHADAP DAYA TAHAN ATLET DHANY’S TAEKWONDO KLUB PEKANBARU - Yana Puspita Arrum; Ramadi Ramadi; Agus Sulastio (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: The problem in this research is that the endurance of Dhany's Taekwondo Club Pekanbaru is still less than optimal. powered up. The purpose of this research was to determine the effect of circuit training exercises on the endurance of Dhany’s Taekwondo Club Pekanbaru. The population in this research was the 6th Dhany’s Taekwondo Club Pekanbaru athlete. In the research the sampling technique used was total sampling, so the samples in this research were 6 people from the Dhany’s Taekwondo Club Pekanbaru. The instruments used to collect data are pre-test and post-endurance test using a 12-minute running test. The data analysis technique used is the t test. The average pretest results of endurance athletes of Dhany’s Taekwondo Club Pekanbaru by running 12 minutes is 1.57 miles and the average results of posttest endurance of athletes of Dhany’s Taekwondo Club Pekanbaru by running 12 minutes are 1.66 miles thus giving a change of 5.28%. Based on the analysis of the data used using the t test, it is known that the test results t count = 10,640 which is greater than t table = 2,015. So it can be concluded that the training circuit training that has been given has a positive impact on endurance. Based on the results of the analysis, it was concluded that there was an effect of circuit training exercises against endurance of Dhany’s Taekwondo Club Pekanbaru athletes.Keywords: Circuit Training Exercises, Endurance